THE METHODOLOGY FOR THE SYNTHESIS AND CORRECTION OF THE "RISK PYRAMIDS" IN THE AIRPLANE SEGMENT OF COMMERCIAL AVIATION OF RUSSIA - A. G. Guziy; A. M. Lushkin; A. V. Fokin (Научный вестник МГТУ ГА, 2018)
The article presents the results of the "risk pyramids" analysis of commercial aviation for their adequacy to the current state of the aviation transport system of Russia. The necessity of annual updating of "risk pyramids" is shown, as the aviation transport system (ATS) of Russia is dynamic and the ATS state changes faster than the accident rate statistical indicators characterizing this state. The method of linear weighted moving average for the synthesis and annual correction of the "risk pyramids" parameters with an optimized averaging coefficient – 7 years is substantiated and proposed. The optimization of the averaging coefficient is performed by the criterion of the minimum mismatch between the averaged values of the "risk pyramids" parameters and the current (annual) values determined by the statistical data of an aviation events. The general and private "risk pyramids" of commercial aviation of Russia synthesized by results of the statistical factorial analysis of aviation events for 2009–2016 are presented. The synthesis of "risk pyramids" is made in accordance with the classification of aviation events in the civil aviation of Russia, separately by causative factors: "Human", "Aircraft", "Environment". The parameters of the "risk pyramids" reflect the conditional probability of an aviation event of great severity (for example, a catastrophe), if there were aviation events of less severity (for example, incidents).  The parameters of the presented pyramids are intended for inclusion into the algorithms of indirect estimation of probability of aviation accidents for any airline and any period of flight work (from a month or more).